2022
DOI: 10.1515/psr-2022-0131
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachtin in the aquatic environment: Fate and effects on non-target fauna

Abstract: The present-day inclination towards increased application of pesticides derived from natural sources is not without its own hazards. Such pesticides are indubitably less harmful compared to the newer classes of low persistence organophosphates; however, these pesticides may be hydrolyzed to yield secondary products which often exhibit significantly different toxicity. Additionally, studies show that the inert materials used in formulation can exhibit significant toxicity on their own. The toxicity of secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In mice, crude ethanol extract of neem (Azadirachta indica) leaves showed a dosedependent increase in both individual (breaks and gaps) and gross (aneuploidy and polyploidy) types of abnormalities in the bone marrow cells and in its pure form, formulation, and crude extracts azadirachtin can produce ecotoxicological consequences including abnormal behaviour, physiological imbalances, and growth inhibition [32][33][34] . Gurme et al 35 reported that 28 M azadirachtin reduced the proportion of dividing cells and induced the formation of micronuclei in TP53 mutant cell lines.…”
Section: Dmso-control (+) Control-cyclophosphamide P -Polychromatic C...mentioning
confidence: 99%
“…In mice, crude ethanol extract of neem (Azadirachta indica) leaves showed a dosedependent increase in both individual (breaks and gaps) and gross (aneuploidy and polyploidy) types of abnormalities in the bone marrow cells and in its pure form, formulation, and crude extracts azadirachtin can produce ecotoxicological consequences including abnormal behaviour, physiological imbalances, and growth inhibition [32][33][34] . Gurme et al 35 reported that 28 M azadirachtin reduced the proportion of dividing cells and induced the formation of micronuclei in TP53 mutant cell lines.…”
Section: Dmso-control (+) Control-cyclophosphamide P -Polychromatic C...mentioning
confidence: 99%